Model Pembinaan Mental dalam Membangun Profesionalitas dan Spiritualitas Prajurit TNI - Ike Lintang Sari; Muhayi, Wafiqotul Wildah; Fadilah, Septiyani Nur (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Abstract: Soldiers must have sufficient abilities from various aspects, such as mental quality and abilities in the field of military operations, such as operational planning, strategic tactics of attack, defense, intelligence, and logistics, as well as the readiness of defense equipment and logistics administration support, which is an important part of the task of maintaining national defense and security. This research aims at a mental development model in building the professionalism and spirituality of TNI soldiers. Researchers used a qualitative descriptive approach. The subjects were Yonif 406/CK Purbalingga staff, Bintal supervisors, soldiers, families, and the community around Yonif 406/CK Purbalingga. Three data collection methods were used in this research: observation, interviews, and documentation. The resulting research data is then analyzed using an interactive analysis model, and then conclusions are drawn. The results of the research show that TNI AD soldiers at Yonif 406/CK Purbalingga receive mental training in accordance with military characteristics, including methods, procedures, and implementation techniques. Mental development has improved the performance of the Indonesian Army at Battalion 406/CK Purbalingga. Mental training is carried out to support the performance of soldiers in carrying. Abstrak: Prajurit harus memiliki kemampuan yang cukup dari berbagai aspek, seperti kualitas mental dan kemampuan di bidang operasi militer, seperti perencanaan operasi, taktik strategi penyerangan, pertahanan, intelijen, dan logistik, serta kesiapan alutsista dan dukungan administrasi logistik, yang menjadi bagian penting dari tugas menjaga pertahanan dan keamanan negara. Penelitian ini bertujuan untuk model pembinaan mental dalam membangun profesionalitas dan spiritualitas prajurit TNI. Peneliti menggunakan pendekatan deskriptif kualitatif. Subyek adalah staf Yonif 406/CK Purbalingga, Pembimbing Bintal, prajurit, keluarga, dan masyarakat di sekitar Yonif 406/CK Purbalingga. Tiga metode pengumpulan data digunakan dalam penelitian ini: observasi, wawancara, dan dokumentasi. Data penelitian yang dihasilkan, kemudian dilakukan analisis data menggunakan model analisis interaktif dan selanjutnya untuk membuat kesimpulan. Hasil studi menunjukkan bahwa prajurit TNI AD di Yonif 406/CK Purbalingga menerima pembinaan mental yang sesuai dengan karakteristik militer, termasuk metode, prosedur, dan teknik pelaksanaannya. Pembinaan mental telah meningkatkan kinerja TNI AD di Yonif 406/CK Purbalingga. Pembinaan mental dilakukan untuk mendukung kinerja prajurit dalam melaksanakan tugas-tugasnya.